Estudo da Influência do Teor de ZrO2-3Y2O3 em Matriz de alfa-Al2O3 - Araujo, Ana Carolina Agrizzi (2022)
Alumina-based ceramics have great relevance as cutting tools materials in the machining process of mainly ferrous materials, due to their wide availability in nature, high hardness and chemical stability at high temperatures, but they have low fracture toughness. One method to increase this property in alumina is the addition of ZrO2 stabilized with Y2O3 (3Y-ZrO2) in the Al2O3 matrix, promoting the toughening effect due to the phase transformation of zirconia, a composite known as zirconia toughened alumina, ZTA. The objective of this work is to study the influence of the 3Y-ZrO2 (nanopowder) content on the Al2O3 matrix (ultrafine powder) using the modern technique of pulsed electric current sintering (PECS) for sample processing. The 3Y-ZrO2 content was changed from 5 to 35% by volume. The powders were sintered at uniaxial pressure of 50 MPa and temperature of 1400ºC. Relative density, Vickers hardness and fracture toughness (KIC) tests were performed and compared with the commercial ceramic used as a reference. A functionally graded material design (Functionally Graded Material, FGM) was made and the residual stress in this was calculated. The results showed, for commercial ceramics, relative density of 98,2 ± 0,3%, Vickers hardness of 1712 ± 306 HV and KIC equal to 4,22 ± 0,67 MPa.m1/2. For the PECS sintered samples, the 3Y-ZrO2 content helped to achieve a total densification starting at 15%ZrO2 content. All samples had a Vickers hardness number greater than the reference. Although the 5%ZrO2 sample had about 8% in porosity, it had the highest hardness number Vickers 2007 ± 35 HV and KIC 5,54 ± 0,42 MPa.m1/2. From regression curves and with the aim of obtaining greater fracture toughness, the content of 9,08%ZrO2 was chosen. Using the Ravichandran residual stress model, a tensile residual stress was observed in the first layer of the designed FGM, but this is below the rupture stresses reported for the same material in the literature. This analysis was important to highlight the adaptation properties of a functionally graded ceramic to be applied as a cutting tool.